Comparative Proteomic, Glycoproteomic And Phosphoproteomic Analyses Of Breast Cancer Tissues - Al-Wajeeh, Abdullah Saleh Saleh Abdullah (2019)
Breast cancer is the second-most leading cause of death among women worldwide. This is true in the Malaysian population as well; breast cancer is one of the most common types of cancer among women. This study was aimed to identify potential tumour proteins that are characteristic of breast carcinogenesis. In order to detect the tumour-specific proteins, differential proteomic profiling was conducted using advanced proteomics techniques in healthy and tumour breast tissue samples. In this study, protein profiles of breast tumour and their adjacent normal tissues from Malaysian women were obtained and examined using GELFREE separation, LTQ-Orbitrap LC-MS/MS identification, and bioinformatic analyses. Findings of the current proteomic profile showed that among the proteins that were detected, several proteins were found with post-translation modifications (PTMs) such as phosphorylation and glycosylation. The analysis of proteins resulted in the identification of 137 proteins, out of that 21 proteins were significantly abundant in tumour tissues. In addition, 81 phosphoproteins were identified, out of that 12 proteins were found significantly higher in abundance in tumour tissues than compared to that their normal counterparts. Furthermore, the analysis identified a total of 73 glycoproteins, out of these 10 glycoproteins were recorded to be significantly abundant in tumour tissues. Generally, most of the identified proteins were found to be involved in physiological processes such as proliferation, cell survival, motility, invasion, angiogenesis, metastasis and stem cell self-renewal and cell structure signalling pathways.